A peptide-based inhibitor of gp96 suppresses HBsAg expression and HBV replication by upregulation of p53. (17th June 2019) - Qian, Liyuan; Fan, Hongxia; Ju, Ying; Chen, Lizhao; Li, Xin; Ye, Xin; Luo, Yunjing; Li, Changfei; Meng, Songdong
Abstract : In hepatitis B virus (HBV) infection, the virus produces redundant hepatitis B surface antigen (HBsAg) that plays a key role in driving T-cell tolerance and viral persistence. However, currently available anti-HBV agents have no direct effect on HBsAg transcription and protein expression. In this study, we designed a heat shock protein gp96 inhibitor p37 with the cell penetrating peptide PTD (protein transduction domain of trans-activator of transcription), which mediated p37 internalization into hepatocytes. PTD-p37 effectively suppressed HBsAg expression and viral replication both in vitro and in vivo . We further provide evidence that PTD-p37 suppressed HBV enhancer/promoter activity via p53 upregulation. Moreover, PTD-p37 had antiviral activity against a lamivudine-resistant HBV strain. Considering that suppression of HBsAg expression is a major goal for treatment of HBV infection, our results provide a basis for developing a new therapeutic approaches targeting host factors against viral expression.